Islamic Ecospirituality and Artificial Intelligence: Toward Ecodigital Awareness in Climate Change Communication - Efendi, Efendi; Suratman, Junizar; Gazali, Gazali; Harlis, Syukri Alfauzi; Hadi, Rahmad Tri; Efendi, Salsa Hamidah; Muhammad Idris (KALAM, 2026)
The global environmental crisis reflects not only ecological degradation but also a moral and spiritual rupture in the human–nature relationship. While artificial intelligence (AI) enhances environmental monitoring, prediction, and communication, it remains largely technocratic and insufficient to foster transformative ecological consciousness. Conversely, eco-spirituality provides ethical depth and moral responsibility but lacks scalable mechanisms for broad societal impact. This study proposes eco-digital consciousness as an integrative framework that synthesizes AI-driven technological mediation with eco-spiritual ethical foundations. Using a conceptual qualitative design, the research combines critical discourse analysis with a multidisciplinary literature review across environmental philosophy, Islamic eco-theology, digital communication, and AI in climate governance. Findings show that AI improves cognitive accessibility and personalized engagement through real-time data and adaptive systems, while eco-spirituality enhances affective depth and ethical orientation. Their integration produces ecological narratives that are cognitively accessible, emotionally resonant, and ethically compelling, shifting environmental communication from information transmission to consciousness transformation. The study conceptualizes eco-digital consciousness across three dimensions: cognitive-digital awareness, affective-spiritual internalization, and ethical-behavioral transformation. It also identifies key shifts in green campaigns, from mass communication to personalization, from awareness to transformation, and from nudging to ethical commitment. Despite AI’s potential, its ethical limitations require eco-spirituality as normative guidance. This framework offers a holistic paradigm for advancing environmental communication and sustainability. [Krisis lingkungan global tidak hanya mencerminkan degradasi ekologis, tetapi juga menunjukkan keretakan moral dan spiritual dalam hubungan manusia dengan alam. Meskipun kecerdasan buatan (AI) meningkatkan pemantauan, prediksi, dan komunikasi lingkungan, pendekatannya masih bersifat teknokratis dan belum mampu mendorong kesadaran ekologis yang transformatif. Sebaliknya, ekospiritualitas memberikan kedalaman etis dan tanggung jawab moral, namun belum memiliki mekanisme yang skalabel untuk menjangkau masyarakat luas. Penelitian ini mengajukan eco-digital consciousness sebagai kerangka integratif yang mensintesis mediasi teknologi berbasis AI dengan fondasi etika ekospiritualitas. Dengan pendekatan kualitatif konseptual, penelitian ini menggabungkan analisis wacana kritis dan tinjauan pustaka multidisipliner yang mencakup filsafat lingkungan, ekoteologi Islam, komunikasi digital, serta AI dalam tata kelola iklim. Hasil penelitian menunjukkan bahwa AI meningkatkan aksesibilitas kognitif dan keterlibatan personal melalui data real-time dan sistem adaptif, sementara ekospiritualitas memperkuat kedalaman afektif dan orientasi etis. Integrasi keduanya menghasilkan narasi ekologis yang mudah dipahami, beresonansi secara emosional, dan kuat secara etis, sehingga menggeser komunikasi lingkungan dari penyampaian informasi menuju transformasi kesadaran. Konsep ini mencakup tiga dimensi: kesadaran kognitif-digital, internalisasi afektif-spiritual, dan transformasi etis-perilaku. Meskipun AI memiliki keterbatasan etis, ekospiritualitas berperan sebagai panduan normatif. Kerangka ini menawarkan paradigma holistik bagi komunikasi lingkungan dan keberlanjutan.]